Synthesis And Characterization Of Complex Diaquadihydantoin Nickel(II) Sulfat Monohidrat - Sentot Budi Rahardjo; Surya Dewi Marliyana; Nur Asih Siwi Wulandari (UNIVERSITAS SEBELAS MARET (UNS), 2014)
The purpose of the research is to find out the synthesis, formula and characteristic of complex of Nickel(II) with hydantoin (hyd). Complex of nickel(II) with hydantoin have been synthesized in 1 : 1 mole ratio of metal to ligan in methanol.The formula of complex which are predicted from analysis of % Ni in complex by Atomic Absorption Spectroscopy (AAS) is Ni(hyd)2(H2O)3.SO4. Ratio of cation and anion of complex is measured by conductivitymeter correspond to 1: 1. The thermal analysis is determined by Differential Thermal Analyser (DTA) indicate that complex contain some hydrate, thus possibility formula of complex is [Ni(hyd)2(H2O)2]SO4.H2O (Diaquadihydantoinnikel(II) sulfat monohidrat). Data of infra red spectra show a shift of N-H group and tertier N group 138 absorption and indicate this functional group coordinated to the center ion. Magnetic Suscepbility measurement show that the complex is paramagnetic with μeff = 3.2 BM. The UV-Vis spectra appear do to 2 transition peak on λ = 740 nm (13,513 cm-1) and 405 nm (24,691 cm-1). The peak indicate that structure of complex is octahedral with transition 3A2g→ 3T1g(P)(ν2) andtransition 3A2g → 3T1g(F)(ν3). One peak which is not appear is transition 3A2g → 3T2g (F)(ν1) which also estimate of 10 Dq (Δ0) is 103.615 kJ mol-1.